American Indian Casinos and Native American Self-Identification - Francisca M. Antman; Brian Duncan (Institute of Labor Economics (IZA), 2023)
This paper links Native American racial self-identification with the rise in tribal gaming across the United States. We find that state policy changes allowing tribes to open casinos are associated with an increase in the probability that individuals with American Indian ancestors will self-identify as Native American and a decrease in the probability that individuals with no American Indian ancestry will self-identify as Native American. Moreover, we find that the magnitudes of the impacts are increasing in the strength of American Indian ancestral ties. Similar results hold when causal identification comes from American Indian casino openings across states over time and suggestive evidence shows stronger impacts if casinos are likely to pay per capita dividend payments to their members. These results are consistent with a conceptual framework in which we tie racial identification to economic motivations as well as social stigma associated with affiliating with a racial group for those without documented ancestral ties. Our results underscore the importance of economic incentives and social factors underlying the individual choice of racial identity.
Keywords: J15; L83; Z13; 330; race; Native American; identity; casinos